Therapeutic Adherence and Subjective Well-being in Patients with Type II Diabetes Mellitus - Ahmed José Pomares Avalos; Rocío Jorge González; Yuslemi Alfonso Trujillo; Marian Amanda Vázquez Núñez (Revista Finlay)
Foundation: the process of patient adherence to medical treatments with chronic conditions is modulated by psychological, cognitive, motivational and volitional factors. Objective: to determine how therapeutic adherence and subjective well-being are manifested in patients with type II diabetes mellitus. Methods: it was conducted a descriptive, cross-sectional study of patients with diabetes mellitus type II, from the Cecilio Ruíz de Zarate health area, Cienfuegos province, in the period from April to May 2018. Simple random sampling was used, with a sample of 30 patients. The variables studied were: age, sex, level of education, occupation, diabetes mellitus, therapeutic adherence and subjective well-being. The instruments for data collection were the questionnaire for the evaluation of the therapeutic adherence Martín, Bayarre and Grau and the reduced scale of subjective well-being. Results: partial adherence to treatment prevailed in the studied patients, as well as the presence of high subjective well-being. Conclusions: the subjective well-being can be a protective factor for the individual´s health before pathological processes, however, it is not necessarily equivalent to present therapeutic adherence, since in the studied patients, despite having a high subjective well-being, difficulties remained in therapeutic adherence.